Genetic and epigenetic studies of adiposity and cardiometabolic disease. - Holmes, M; Pulit, S; Lindgren, C (BioMed Central, 2017)
Over 300 million adults are obese, but little is known about the impact of obesity on cardiovascular health. We discuss recent genetic and epigenetic studies of adiposity that indicate a causal role for general and central adiposity in cardiometabolic disease, and highlight potential mechanisms including insulin resistance and gene expression.